1970
DOI: 10.2134/agronj1970.00021962006200010009x
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Soil Moisture Stress on the Growth of Wheat (Triticum aestivum L. em Thell.)1

Abstract: Investigations were conducted in 1966 and 1967 at Tucson, Ariz., to study some effects of soil‐moisture stress, at three different stages of development (jointing, flowering, and dough) on the growth and grain yield of spring wheat (Triticum aestivum L. em Thell.) planted in December. A critical period in the growth of wheat was the jointing stage for moisture. Stressing wheat for water at jointing resulted in fewer days from planting to flowering, shorter plants, more lodging, lower grain yield, lower grain v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 5 publications
8
39
0
1
Order By: Relevance
“…On the basis of the results obtained in both Experiments 1 and 2, it was concluded that the optimum irrigation period to increase the grain yield of this cultivar extended from the beginning of tillering to the heading stage, presumably due to the increase in the effect of irrigation on the number of effective spikes per unit area. This optimum irrigation period and the effect of irrigation in the optimum period on the yield components are consistent with the conclusion of the report by Salter and Goode (1967), and other researchers (Kusunoki et al 1960;Day and Intalap 1970;Musick and Dusek 1980;Singh 1981;Hooker et al 1983).…”
Section: Discussionsupporting
confidence: 91%
“…On the basis of the results obtained in both Experiments 1 and 2, it was concluded that the optimum irrigation period to increase the grain yield of this cultivar extended from the beginning of tillering to the heading stage, presumably due to the increase in the effect of irrigation on the number of effective spikes per unit area. This optimum irrigation period and the effect of irrigation in the optimum period on the yield components are consistent with the conclusion of the report by Salter and Goode (1967), and other researchers (Kusunoki et al 1960;Day and Intalap 1970;Musick and Dusek 1980;Singh 1981;Hooker et al 1983).…”
Section: Discussionsupporting
confidence: 91%
“…Moisture stress at different stages of plant development resulted in the greatest reduction in grain-volume weight (Day and Intlap 1970). The wheat plants growing under water stress Table 2 that the heritability estimates for 1000-grain weight were high in order.…”
Section: Resultsmentioning
confidence: 93%
“…The height of the culms, size of the leaves, the distance between the veins and the stomata openings are all affected when they are developing under limited water supplies. When wheat plants are stressed for water at vegetative and flowering stages, shorter plants are obtained, as a result of low moisture absorption, lower soil nutrient uptake, reduced cell size and reduced photosynthesis (Day and Intlap 1970;Sheikh et al 2000). Heritability estimates computed for plant height in present study are in accordance with the findings of Fedin (1976) who reported high heritability estimates for this character.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations